Hand bone age a digital atlas of skeletal maturity - Gilsanz, Vicente (Springer Berlin Heidelberg :, 2012)
In the past, determination of bone maturity relied on visual evaluation of skeletal development in the hand and wrist, most commonly using the Greulich and Pyle atlas. The Gilsanz and Ratib digital atlas takes advantage of digital imaging and provides a more effective and objective approach to assessment of skeletal maturity. The atlas integrates the key morphological features of ossification in the bones of the hand and wrist and provides idealized, sex- and age-specific images of skeletal development. New to this revised second edition is a description and user manual for Bone Age for iPad®, iPhone® and iPod touch®, which can be purchased and used separately from this book. Bone Age enables users to rapidly browse through the set of idealized atlas images and select the one that best matches the image being interpreted. The calculated deviation of the patient's age from the normal range is immediately presented to help predict possible growth delays. This easy-to-use atlas and the related App will be invaluable for radiologists, endocrinologists, and pediatricians and also relevant to forensic physicians. Introduction -- Bone Development -- Clinical Applications for Skeletal Determinations -- Cenventional Techniques for Skeletal Determinations -- Computer Assisted Techniques for Skeletal Determinations -- Indicators of Skeletal maturity in Children and Adolescents -- Digital Bone Age Atlas -- iPhone / iPad App User Manual -- Reference Images -- Tables.